LENGTH-WEIGHT RELATIONSHIP OF CYNOGLOSSUS LIDA (BLEEKER) - Seshappa, G; Chakrapani, B K (Indian Journal of Fisheries, 2011)
Studies on Length-Weight (relationships of fishes have been recognized asimportant aspects in fishery biology stodias. Some of- the more important Indianworks in. this line 'have been mentioned by Seshappa, while giving an accountof the length-weight relationships of three species of tongue soles, namely,Cynoglossus Semifasciatus (Day), C. dubius (Day) and C. bilineatus (Lacepede)at Calicut (Seshappa, in Press). Among the more recent papers in this line maybe mentioned those of Hussain and AbduUa (1977), Ghatterji (1980), Soniand Kumari Maya Katbal (1979), Rita Kuimari and Balakdshnan Nair (1978),Dan and Mojumder (1978), and Victor (1978).